Pathological Diagnosis of Hepatocellular Cellular Adenoma according to the Clinical Context - Paulette Bioulac-Sage; Christine Sempoux; Laurent Possenti; Nora Frulio; Hervé Laumonier; Christophe Laurent; Laurence Chiche; Jean Frédéric Blanc; Jean Saric; Hervé Trillaud; Brigitte Le Bail; Charles Balabaud (International Journal of Hepatology)
In Europe and North America, hepatocellular adenomas (HCA) occur, classically, in middle-aged woman taking oral contraceptives. Twenty percent of women, however, are not exposed to oral contraceptives; HCA can more rarely occur in men, children, and women over 65 years. HCA have been observed in many pathological conditions such as glycogenosis, familial adenomatous polyposis, MODY3, after male hormone administration, and in vascular diseases. Obesity is frequent particularly in inflammatory HCA. The background liver is often normal, but steatosis is a frequent finding particularly in inflammatory HCA. The diagnosis of HCA is more difficult when the background liver is fibrotic, notably in vascular diseases. HCA can be solitary, or multiple or in great number (adenomatosis). When nodules are multiple, they are usually of the same subtype. HNF1α-inactivated HCA occur almost exclusively in woman. The most important point of the classification is the identification of β-catenin mutated HCA, a strong argument to identify patients at risk of malignant transformation. Some HCA already present criteria indicating malignant transformation. When the whole nodule is a hepatocellular carcinoma, it is extremely difficult to prove that it is the consequence of a former HCA. It is occasionally difficult to identify HCA remodeled by necrosis or hemorrhage.